Leaf Impression of Amesoneuron (Arecaceae) from the Lower Siwalik Sediments of the Kankai Mai River Section, Eastern Nepal - Adhikari, Purushottam; Khatri, Dhan Bahadur; Srivastava, Gaurav; Paudayal, Khum N. (BMC Journal of Scientific Research, 2022)
A leaf impression of Amesoneuron (Arecaceae) is reported from the Lower Siwalik sediments of the Kankai Mai River section, eastern Nepal. The overall habit, habitat and modern distributions and climatic conditions show the existence of tropical to sub-tropical wet evergreen forests with humid swampy lowland areas during the deposition of the sediments.